feat(library/standard/data/quotient): import quotient from lean 0.1
This commit is contained in:
parent
f5987b7bda
commit
ad26c7c93c
7 changed files with 687 additions and 35 deletions
|
@ -1,6 +1,6 @@
|
||||||
-- Copyright (c) 2014 Microsoft Corporation. All rights reserved.
|
-- Copyright (c) 2014 Microsoft Corporation. All rights reserved.
|
||||||
-- Released under Apache 2.0 license as described in the file LICENSE.
|
-- Released under Apache 2.0 license as described in the file LICENSE.
|
||||||
-- Author: Leonardo de Moura
|
-- Author: Leonardo de Moura, Jeremy Avigad
|
||||||
|
|
||||||
import logic.classes.inhabited logic.connectives.eq
|
import logic.classes.inhabited logic.connectives.eq
|
||||||
|
|
||||||
|
@ -32,11 +32,11 @@ section
|
||||||
theorem prod_ext (p : prod A B) : pair (pr1 p) (pr2 p) = p :=
|
theorem prod_ext (p : prod A B) : pair (pr1 p) (pr2 p) = p :=
|
||||||
pair_destruct p (λx y, refl (x, y))
|
pair_destruct p (λx y, refl (x, y))
|
||||||
|
|
||||||
theorem pair_eq {p1 p2 : prod A B} (H1 : pr1 p1 = pr1 p2) (H2 : pr2 p1 = pr2 p2) : p1 = p2 :=
|
theorem pair_eq {a1 a2 : A} {b1 b2 : B} (H1 : a1 = a2) (H2 : b1 = b2) : (a1, b1) = (a2, b2) :=
|
||||||
calc p1 = pair (pr1 p1) (pr2 p1) : symm (prod_ext p1)
|
subst H1 (subst H2 (refl _))
|
||||||
... = pair (pr1 p2) (pr2 p1) : {H1}
|
|
||||||
... = pair (pr1 p2) (pr2 p2) : {H2}
|
theorem prod_eq {p1 p2 : prod A B} : ∀ (H1 : pr1 p1 = pr1 p2) (H2 : pr2 p1 = pr2 p2), p1 = p2 :=
|
||||||
... = p2 : prod_ext p2
|
pair_destruct p1 (take a1 b1, pair_destruct p2 (take a2 b2 H1 H2, pair_eq H1 H2))
|
||||||
|
|
||||||
theorem prod_inhabited (H1 : inhabited A) (H2 : inhabited B) : inhabited (prod A B) :=
|
theorem prod_inhabited (H1 : inhabited A) (H2 : inhabited B) : inhabited (prod A B) :=
|
||||||
inhabited_elim H1 (λa, inhabited_elim H2 (λb, inhabited_intro (pair a b)))
|
inhabited_elim H1 (λa, inhabited_elim H2 (λb, inhabited_intro (pair a b)))
|
||||||
|
|
599
library/standard/data/quotient.lean
Normal file
599
library/standard/data/quotient.lean
Normal file
|
@ -0,0 +1,599 @@
|
||||||
|
-- Copyright (c) 2014 Floris van Doorn. All rights reserved.
|
||||||
|
-- Released under Apache 2.0 license as described in the file LICENSE.
|
||||||
|
-- Author: Floris van Doorn
|
||||||
|
|
||||||
|
import logic tools.tactic .subtype logic.connectives.cast struc.relation data.prod
|
||||||
|
import logic.connectives.instances
|
||||||
|
|
||||||
|
-- for now: to use substitution (iff_to_eq)
|
||||||
|
import logic.axioms.classical
|
||||||
|
|
||||||
|
-- for the last section
|
||||||
|
import logic.axioms.hilbert logic.axioms.funext
|
||||||
|
|
||||||
|
using relation prod tactic eq_proofs
|
||||||
|
|
||||||
|
|
||||||
|
-- temporary: substiution for iff
|
||||||
|
theorem substi {a b : Prop} {P : Prop → Prop} (H1 : a ↔ b) (H2 : P a) : P b :=
|
||||||
|
subst (iff_to_eq H1) H2
|
||||||
|
|
||||||
|
theorem transi {a b c : Prop} (H1 : a ↔ b) (H2 : b ↔ c) : a ↔ c :=
|
||||||
|
eq_to_iff (trans (iff_to_eq H1) (iff_to_eq H2))
|
||||||
|
|
||||||
|
theorem symmi {a b : Prop} (H : a ↔ b) : b ↔ a :=
|
||||||
|
eq_to_iff (symm (iff_to_eq H))
|
||||||
|
|
||||||
|
-- until we have the simplifier...
|
||||||
|
definition simp : tactic := apply @sorry
|
||||||
|
|
||||||
|
|
||||||
|
-- TODO: find a better name, and move to logic.connectives.basic
|
||||||
|
theorem and_inhabited_left {a : Prop} (b : Prop) (Ha : a) : a ∧ b ↔ b :=
|
||||||
|
iff_intro (take Hab, and_elim_right Hab) (take Hb, and_intro Ha Hb)
|
||||||
|
|
||||||
|
|
||||||
|
-- auxliary facts about products
|
||||||
|
-- -----------------------------
|
||||||
|
|
||||||
|
-- TODO: move to data.prod?
|
||||||
|
|
||||||
|
-- ### flip
|
||||||
|
|
||||||
|
definition flip {A B : Type} (a : A × B) : B × A := pair (pr2 a) (pr1 a)
|
||||||
|
|
||||||
|
theorem flip_def {A B : Type} (a : A × B) : flip a = pair (pr2 a) (pr1 a) := refl (flip a)
|
||||||
|
|
||||||
|
theorem flip_pair {A B : Type} (a : A) (b : B) : flip (pair a b) = pair b a := rfl
|
||||||
|
|
||||||
|
theorem flip_pr1 {A B : Type} (a : A × B) : pr1 (flip a) = pr2 a := rfl
|
||||||
|
|
||||||
|
theorem flip_pr2 {A B : Type} (a : A × B) : pr2 (flip a) = pr1 a := rfl
|
||||||
|
|
||||||
|
theorem flip_flip {A B : Type} (a : A × B) : flip (flip a) = a :=
|
||||||
|
pair_destruct a (take x y, rfl)
|
||||||
|
|
||||||
|
theorem P_flip {A B : Type} {P : A → B → Prop} {a : A × B} (H : P (pr1 a) (pr2 a))
|
||||||
|
: P (pr2 (flip a)) (pr1 (flip a)) :=
|
||||||
|
(symm (flip_pr1 a)) ▸ (symm (flip_pr2 a)) ▸ H
|
||||||
|
|
||||||
|
theorem flip_inj {A B : Type} {a b : A × B} (H : flip a = flip b) : a = b :=
|
||||||
|
have H2 : flip (flip a) = flip (flip b), from congr2 flip H,
|
||||||
|
show a = b, from (flip_flip a) ▸ (flip_flip b) ▸ H2
|
||||||
|
|
||||||
|
-- ### coordinatewise unary maps
|
||||||
|
|
||||||
|
definition map_pair {A B : Type} (f : A → B) (a : A × A) : B × B :=
|
||||||
|
pair (f (pr1 a)) (f (pr2 a))
|
||||||
|
|
||||||
|
theorem map_pair_def {A B : Type} (f : A → B) (a : A × A)
|
||||||
|
: map_pair f a = pair (f (pr1 a)) (f (pr2 a)) :=
|
||||||
|
rfl
|
||||||
|
|
||||||
|
theorem map_pair_pair {A B : Type} (f : A → B) (a a' : A)
|
||||||
|
: map_pair f (pair a a') = pair (f a) (f a') :=
|
||||||
|
(pr1_pair a a') ▸ (pr2_pair a a') ▸ (rfl)
|
||||||
|
|
||||||
|
theorem map_pair_pr1 {A B : Type} (f : A → B) (a : A × A) : pr1 (map_pair f a) = f (pr1 a)
|
||||||
|
:= pr1_pair _ _
|
||||||
|
|
||||||
|
theorem map_pair_pr2 {A B : Type} (f : A → B) (a : A × A) : pr2 (map_pair f a) = f (pr2 a)
|
||||||
|
:= pr2_pair _ _
|
||||||
|
|
||||||
|
-- ### coordinatewise binary maps
|
||||||
|
|
||||||
|
definition map_pair2 {A B C : Type} (f : A → B → C) (a : A × A) (b : B × B) : C × C
|
||||||
|
:= pair (f (pr1 a) (pr1 b)) (f (pr2 a) (pr2 b))
|
||||||
|
|
||||||
|
theorem map_pair2_def {A B C : Type} (f : A → B → C) (a : A × A) (b : B × B)
|
||||||
|
: map_pair2 f a b = pair (f (pr1 a) (pr1 b)) (f (pr2 a) (pr2 b)) := rfl
|
||||||
|
|
||||||
|
theorem map_pair2_pair {A B C : Type} (f : A → B → C) (a a' : A) (b b' : B)
|
||||||
|
: map_pair2 f (pair a a') (pair b b') = pair (f a b) (f a' b') :=
|
||||||
|
calc
|
||||||
|
map_pair2 f (pair a a') (pair b b')
|
||||||
|
= pair (f (pr1 (pair a a')) b) (f (pr2 (pair a a')) (pr2 (pair b b')))
|
||||||
|
: {pr1_pair b b'}
|
||||||
|
... = pair (f (pr1 (pair a a')) b) (f (pr2 (pair a a')) b') : {pr2_pair b b'}
|
||||||
|
... = pair (f (pr1 (pair a a')) b) (f a' b') : {pr2_pair a a'}
|
||||||
|
... = pair (f a b) (f a' b') : {pr1_pair a a'}
|
||||||
|
|
||||||
|
theorem map_pair2_pr1 {A B C : Type} (f : A → B → C) (a : A × A) (b : B × B)
|
||||||
|
: pr1 (map_pair2 f a b) = f (pr1 a) (pr1 b) := pr1_pair _ _
|
||||||
|
|
||||||
|
theorem map_pair2_pr2 {A B C : Type} (f : A → B → C) (a : A × A) (b : B × B)
|
||||||
|
: pr2 (map_pair2 f a b) = f (pr2 a) (pr2 b) := pr2_pair _ _
|
||||||
|
|
||||||
|
theorem map_pair2_flip {A B C : Type} (f : A → B → C) (a : A × A) (b : B × B)
|
||||||
|
: flip (map_pair2 f a b) = map_pair2 f (flip a) (flip b) :=
|
||||||
|
have Hx : pr1 (flip (map_pair2 f a b)) = pr1 (map_pair2 f (flip a) (flip b)), from
|
||||||
|
calc
|
||||||
|
pr1 (flip (map_pair2 f a b)) = pr2 (map_pair2 f a b) : flip_pr1 _
|
||||||
|
... = f (pr2 a) (pr2 b) : map_pair2_pr2 f a b
|
||||||
|
... = f (pr1 (flip a)) (pr2 b) : {symm (flip_pr1 a)}
|
||||||
|
... = f (pr1 (flip a)) (pr1 (flip b)) : {symm (flip_pr1 b)}
|
||||||
|
... = pr1 (map_pair2 f (flip a) (flip b)) : symm (map_pair2_pr1 f _ _),
|
||||||
|
have Hy : pr2 (flip (map_pair2 f a b)) = pr2 (map_pair2 f (flip a) (flip b)), from
|
||||||
|
calc
|
||||||
|
pr2 (flip (map_pair2 f a b)) = pr1 (map_pair2 f a b) : flip_pr2 _
|
||||||
|
... = f (pr1 a) (pr1 b) : map_pair2_pr1 f a b
|
||||||
|
... = f (pr2 (flip a)) (pr1 b) : {symm (flip_pr2 a)}
|
||||||
|
... = f (pr2 (flip a)) (pr2 (flip b)) : {symm (flip_pr2 b)}
|
||||||
|
... = pr2 (map_pair2 f (flip a) (flip b)) : symm (map_pair2_pr2 f _ _),
|
||||||
|
pair_eq Hx Hy
|
||||||
|
|
||||||
|
-- add_rewrite flip_pr1 flip_pr2 flip_pair
|
||||||
|
-- add_rewrite map_pair_pr1 map_pair_pr2 map_pair_pair
|
||||||
|
-- add_rewrite map_pair2_pr1 map_pair2_pr2 map_pair2_pair
|
||||||
|
|
||||||
|
theorem map_pair2_comm {A B : Type} {f : A → A → B} (Hcomm : ∀a b : A, f a b = f b a)
|
||||||
|
(v w : A × A) : map_pair2 f v w = map_pair2 f w v :=
|
||||||
|
have Hx : pr1 (map_pair2 f v w) = pr1 (map_pair2 f w v), from
|
||||||
|
calc
|
||||||
|
pr1 (map_pair2 f v w) = f (pr1 v) (pr1 w) : map_pair2_pr1 f v w
|
||||||
|
... = f (pr1 w) (pr1 v) : Hcomm _ _
|
||||||
|
... = pr1 (map_pair2 f w v) : symm (map_pair2_pr1 f w v),
|
||||||
|
have Hy : pr2 (map_pair2 f v w) = pr2 (map_pair2 f w v), from
|
||||||
|
calc
|
||||||
|
pr2 (map_pair2 f v w) = f (pr2 v) (pr2 w) : map_pair2_pr2 f v w
|
||||||
|
... = f (pr2 w) (pr2 v) : Hcomm _ _
|
||||||
|
... = pr2 (map_pair2 f w v) : symm (map_pair2_pr2 f w v),
|
||||||
|
pair_eq Hx Hy
|
||||||
|
|
||||||
|
theorem map_pair2_assoc {A : Type} {f : A → A → A}
|
||||||
|
(Hassoc : ∀a b c : A, f (f a b) c = f a (f b c)) (u v w : A × A) :
|
||||||
|
map_pair2 f (map_pair2 f u v) w = map_pair2 f u (map_pair2 f v w) :=
|
||||||
|
have Hx : pr1 (map_pair2 f (map_pair2 f u v) w) =
|
||||||
|
pr1 (map_pair2 f u (map_pair2 f v w)), from
|
||||||
|
calc
|
||||||
|
pr1 (map_pair2 f (map_pair2 f u v) w)
|
||||||
|
= f (pr1 (map_pair2 f u v)) (pr1 w) : map_pair2_pr1 f _ _
|
||||||
|
... = f (f (pr1 u) (pr1 v)) (pr1 w) : {map_pair2_pr1 f _ _}
|
||||||
|
... = f (pr1 u) (f (pr1 v) (pr1 w)) : Hassoc (pr1 u) (pr1 v) (pr1 w)
|
||||||
|
... = f (pr1 u) (pr1 (map_pair2 f v w)) : {symm (map_pair2_pr1 f _ _)}
|
||||||
|
... = pr1 (map_pair2 f u (map_pair2 f v w)) : symm (map_pair2_pr1 f _ _),
|
||||||
|
have Hy : pr2 (map_pair2 f (map_pair2 f u v) w) =
|
||||||
|
pr2 (map_pair2 f u (map_pair2 f v w)), from
|
||||||
|
calc
|
||||||
|
pr2 (map_pair2 f (map_pair2 f u v) w)
|
||||||
|
= f (pr2 (map_pair2 f u v)) (pr2 w) : map_pair2_pr2 f _ _
|
||||||
|
... = f (f (pr2 u) (pr2 v)) (pr2 w) : {map_pair2_pr2 f _ _}
|
||||||
|
... = f (pr2 u) (f (pr2 v) (pr2 w)) : Hassoc (pr2 u) (pr2 v) (pr2 w)
|
||||||
|
... = f (pr2 u) (pr2 (map_pair2 f v w)) : {symm (map_pair2_pr2 f _ _)}
|
||||||
|
... = pr2 (map_pair2 f u (map_pair2 f v w)) : symm (map_pair2_pr2 f _ _),
|
||||||
|
pair_eq Hx Hy
|
||||||
|
|
||||||
|
theorem map_pair2_id_right {A B : Type} {f : A → B → A} {e : B} (Hid : ∀a : A, f a e = a)
|
||||||
|
(v : A × A) : map_pair2 f v (pair e e) = v :=
|
||||||
|
have Hx : pr1 (map_pair2 f v (pair e e)) = pr1 v, from
|
||||||
|
(calc
|
||||||
|
pr1 (map_pair2 f v (pair e e)) = f (pr1 v) (pr1 (pair e e)) : by simp
|
||||||
|
... = f (pr1 v) e : by simp
|
||||||
|
... = pr1 v : Hid (pr1 v)),
|
||||||
|
have Hy : pr2 (map_pair2 f v (pair e e)) = pr2 v, from
|
||||||
|
(calc
|
||||||
|
pr2 (map_pair2 f v (pair e e)) = f (pr2 v) (pr2 (pair e e)) : by simp
|
||||||
|
... = f (pr2 v) e : by simp
|
||||||
|
... = pr2 v : Hid (pr2 v)),
|
||||||
|
prod_eq Hx Hy
|
||||||
|
|
||||||
|
theorem map_pair2_id_left {A B : Type} {f : B → A → A} {e : B} (Hid : ∀a : A, f e a = a)
|
||||||
|
(v : A × A) : map_pair2 f (pair e e) v = v :=
|
||||||
|
have Hx : pr1 (map_pair2 f (pair e e) v) = pr1 v, from
|
||||||
|
calc
|
||||||
|
pr1 (map_pair2 f (pair e e) v) = f (pr1 (pair e e)) (pr1 v) : by simp
|
||||||
|
... = f e (pr1 v) : by simp
|
||||||
|
... = pr1 v : Hid (pr1 v),
|
||||||
|
have Hy : pr2 (map_pair2 f (pair e e) v) = pr2 v, from
|
||||||
|
calc
|
||||||
|
pr2 (map_pair2 f (pair e e) v) = f (pr2 (pair e e)) (pr2 v) : by simp
|
||||||
|
... = f e (pr2 v) : by simp
|
||||||
|
... = pr2 v : Hid (pr2 v),
|
||||||
|
prod_eq Hx Hy
|
||||||
|
|
||||||
|
opaque_hint (hiding flip map_pair map_pair2)
|
||||||
|
|
||||||
|
|
||||||
|
-- Theory data.quotient
|
||||||
|
-- ====================
|
||||||
|
|
||||||
|
namespace quotient
|
||||||
|
|
||||||
|
using subtype
|
||||||
|
|
||||||
|
-- definition and basics
|
||||||
|
-- ---------------------
|
||||||
|
|
||||||
|
-- TODO: make this a structure
|
||||||
|
definition is_quotient {A B : Type} (R : A → A → Prop) (abs : A → B) (rep : B → A) : Prop :=
|
||||||
|
(∀b, abs (rep b) = b) ∧
|
||||||
|
(∀b, R (rep b) (rep b)) ∧
|
||||||
|
(∀r s, R r s ↔ (R r r ∧ R s s ∧ abs r = abs s))
|
||||||
|
|
||||||
|
theorem intro {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(H1 : ∀b, abs (rep b) = b) (H2 : ∀b, R (rep b) (rep b))
|
||||||
|
(H3 : ∀r s, R r s ↔ (R r r ∧ R s s ∧ abs r = abs s)) : is_quotient R abs rep :=
|
||||||
|
and_intro H1 (and_intro H2 H3)
|
||||||
|
|
||||||
|
-- theorem intro_refl {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
-- (H1 : reflexive R) (H2 : ∀b, abs (rep b) = b)
|
||||||
|
-- (H3 : ∀r s, R r s ↔ abs r = abs s) : is_quotient R abs rep :=
|
||||||
|
-- intro
|
||||||
|
-- H2
|
||||||
|
-- (take b, H1 (rep b))
|
||||||
|
-- (take r s,
|
||||||
|
-- have H4 : R r s ↔ R s s ∧ abs r = abs s,
|
||||||
|
-- from
|
||||||
|
-- gensubst.subst (relation.operations.symm (and_inhabited_left _ (H1 s))) (H3 r s),
|
||||||
|
-- gensubst.subst (relation.operations.symm (and_inhabited_left _ (H1 r))) H4)
|
||||||
|
|
||||||
|
-- these work now, but the above still does not
|
||||||
|
-- theorem test (a b c : Prop) (P : Prop → Prop) (H1 : a ↔ b) (H2 : c ∧ a) : c ∧ b :=
|
||||||
|
-- gensubst.subst H1 H2
|
||||||
|
|
||||||
|
-- theorem test2 {A : Type} {R : A → A → Prop} (Q : Prop) (r s : A)
|
||||||
|
-- (H3 : R r s ↔ Q) (H1 : R s s) : Q ↔ (R s s ∧ Q) :=
|
||||||
|
-- relation.operations.symm (and_inhabited_left Q H1)
|
||||||
|
|
||||||
|
-- theorem test3 {A : Type} {R : A → A → Prop} (Q : Prop) (r s : A)
|
||||||
|
-- (H3 : R r s ↔ Q) (H1 : R s s) : R r s ↔ (R s s ∧ Q) :=
|
||||||
|
-- gensubst.subst (test2 Q r s H3 H1) H3
|
||||||
|
|
||||||
|
-- theorem test4 {A : Type} {R : A → A → Prop} (Q : Prop) (r s : A)
|
||||||
|
-- (H3 : R r s ↔ Q) (H1 : R s s) : R r s ↔ (R s s ∧ Q) :=
|
||||||
|
-- gensubst.subst (relation.operations.symm (and_inhabited_left Q H1)) H3
|
||||||
|
|
||||||
|
theorem intro_refl {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(H1 : reflexive R) (H2 : ∀b, abs (rep b) = b)
|
||||||
|
(H3 : ∀r s, R r s ↔ abs r = abs s) : is_quotient R abs rep :=
|
||||||
|
intro
|
||||||
|
H2
|
||||||
|
(take b, H1 (rep b))
|
||||||
|
(take r s,
|
||||||
|
have H4 : R r s ↔ R s s ∧ abs r = abs s,
|
||||||
|
from
|
||||||
|
substi (symmi (and_inhabited_left _ (H1 s))) (H3 r s),
|
||||||
|
substi (symmi (and_inhabited_left _ (H1 r))) H4)
|
||||||
|
|
||||||
|
theorem abs_rep {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(Q : is_quotient R abs rep) (b : B) : abs (rep b) = b :=
|
||||||
|
and_elim_left Q b
|
||||||
|
|
||||||
|
theorem refl_rep {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(Q : is_quotient R abs rep) (b : B) : R (rep b) (rep b) :=
|
||||||
|
and_elim_left (and_elim_right Q) b
|
||||||
|
|
||||||
|
theorem R_iff {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(Q : is_quotient R abs rep) (r s : A) : R r s ↔ (R r r ∧ R s s ∧ abs r = abs s) :=
|
||||||
|
and_elim_right (and_elim_right Q) r s
|
||||||
|
|
||||||
|
theorem refl_left {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(Q : is_quotient R abs rep) {r s : A} (H : R r s) : R r r :=
|
||||||
|
and_elim_left (iff_elim_left (R_iff Q r s) H)
|
||||||
|
|
||||||
|
theorem refl_right {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(Q : is_quotient R abs rep) {r s : A} (H : R r s) : R s s :=
|
||||||
|
and_elim_left (and_elim_right (iff_elim_left (R_iff Q r s) H))
|
||||||
|
|
||||||
|
theorem eq_abs {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(Q : is_quotient R abs rep) {r s : A} (H : R r s) : abs r = abs s :=
|
||||||
|
and_elim_right (and_elim_right (iff_elim_left (R_iff Q r s) H))
|
||||||
|
|
||||||
|
theorem R_intro {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(Q : is_quotient R abs rep) {r s : A} (H1 : R r r) (H2 : R s s) (H3 : abs r = abs s) : R r s :=
|
||||||
|
iff_elim_right (R_iff Q r s) (and_intro H1 (and_intro H2 H3))
|
||||||
|
|
||||||
|
theorem R_intro_refl {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(Q : is_quotient R abs rep) (H1 : reflexive R) {r s : A} (H2 : abs r = abs s) : R r s :=
|
||||||
|
iff_elim_right (R_iff Q r s) (and_intro (H1 r) (and_intro (H1 s) H2))
|
||||||
|
|
||||||
|
theorem rep_eq {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(Q : is_quotient R abs rep) {a b : B} (H : R (rep a) (rep b)) : a = b :=
|
||||||
|
calc
|
||||||
|
a = abs (rep a) : symm (abs_rep Q a)
|
||||||
|
... = abs (rep b) : {eq_abs Q H}
|
||||||
|
... = b : abs_rep Q b
|
||||||
|
|
||||||
|
theorem R_rep_abs {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(Q : is_quotient R abs rep) {a : A} (H : R a a) : R a (rep (abs a)) :=
|
||||||
|
have H3 : abs a = abs (rep (abs a)), from symm (abs_rep Q (abs a)),
|
||||||
|
R_intro Q H (refl_rep Q (abs a)) H3
|
||||||
|
|
||||||
|
theorem quotient_imp_symm {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(Q : is_quotient R abs rep) : symmetric R :=
|
||||||
|
take a b : A,
|
||||||
|
assume H : R a b,
|
||||||
|
have Ha : R a a, from refl_left Q H,
|
||||||
|
have Hb : R b b, from refl_right Q H,
|
||||||
|
have Hab : abs b = abs a, from symm (eq_abs Q H),
|
||||||
|
R_intro Q Hb Ha Hab
|
||||||
|
|
||||||
|
theorem quotient_imp_trans {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(Q : is_quotient R abs rep) : transitive R :=
|
||||||
|
take a b c : A,
|
||||||
|
assume Hab : R a b,
|
||||||
|
assume Hbc : R b c,
|
||||||
|
have Ha : R a a, from refl_left Q Hab,
|
||||||
|
have Hc : R c c, from refl_right Q Hbc,
|
||||||
|
have Hac : abs a = abs c, from trans (eq_abs Q Hab) (eq_abs Q Hbc),
|
||||||
|
R_intro Q Ha Hc Hac
|
||||||
|
|
||||||
|
-- recursion
|
||||||
|
-- ---------
|
||||||
|
|
||||||
|
-- (maybe some are superfluous)
|
||||||
|
|
||||||
|
definition rec {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(Q : is_quotient R abs rep) {C : B → Type} (f : forall (a : A), C (abs a)) (b : B) : C b :=
|
||||||
|
eq_rec_on (abs_rep Q b) (f (rep b))
|
||||||
|
|
||||||
|
theorem comp {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(Q : is_quotient R abs rep) {C : B → Type} {f : forall (a : A), C (abs a)}
|
||||||
|
(H : forall (r s : A) (H' : R r s), eq_rec_on (eq_abs Q H') (f r) = f s)
|
||||||
|
{a : A} (Ha : R a a) : rec Q f (abs a) = f a :=
|
||||||
|
have H2 [fact] : R a (rep (abs a)), from R_rep_abs Q Ha,
|
||||||
|
calc
|
||||||
|
rec Q f (abs a) = eq_rec_on _ (f (rep (abs a))) : rfl
|
||||||
|
... = eq_rec_on _ (eq_rec_on _ (f a)) : {symm (H _ _ H2)}
|
||||||
|
... = eq_rec_on _ (f a) : eq_rec_on_compose _ _ _
|
||||||
|
... = f a : eq_rec_on_id _ _
|
||||||
|
|
||||||
|
definition rec_constant {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(Q : is_quotient R abs rep) {C : Type} (f : A → C) (b : B) : C :=
|
||||||
|
f (rep b)
|
||||||
|
|
||||||
|
theorem comp_constant {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(Q : is_quotient R abs rep) {C : Type} {f : A → C}
|
||||||
|
(H : forall (r s : A) (H' : R r s), f r = f s)
|
||||||
|
{a : A} (Ha : R a a) : rec_constant Q f (abs a) = f a :=
|
||||||
|
have H2 : R a (rep (abs a)), from R_rep_abs Q Ha,
|
||||||
|
calc
|
||||||
|
rec_constant Q f (abs a) = f (rep (abs a)) : rfl
|
||||||
|
... = f a : {symm (H _ _ H2)}
|
||||||
|
|
||||||
|
definition rec_binary {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(Q : is_quotient R abs rep) {C : Type} (f : A → A → C) (b c : B) : C :=
|
||||||
|
f (rep b) (rep c)
|
||||||
|
|
||||||
|
theorem comp_binary {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(Q : is_quotient R abs rep) {C : Type} {f : A → A → C}
|
||||||
|
(H : forall (a a' b b' : A) (Ha : R a a') (Hb : R b b'), f a b = f a' b')
|
||||||
|
{a b : A} (Ha : R a a) (Hb : R b b) : rec_binary Q f (abs a) (abs b) = f a b :=
|
||||||
|
have H2 : R a (rep (abs a)), from R_rep_abs Q Ha,
|
||||||
|
have H3 : R b (rep (abs b)), from R_rep_abs Q Hb,
|
||||||
|
calc
|
||||||
|
rec_binary Q f (abs a) (abs b) = f (rep (abs a)) (rep (abs b)) : rfl
|
||||||
|
... = f a b : {symm (H _ _ _ _ H2 H3)}
|
||||||
|
|
||||||
|
theorem comp_binary_refl {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(Q : is_quotient R abs rep) (Hrefl : reflexive R) {C : Type} {f : A → A → C}
|
||||||
|
(H : forall (a a' b b' : A) (Ha : R a a') (Hb : R b b'), f a b = f a' b')
|
||||||
|
(a b : A) : rec_binary Q f (abs a) (abs b) = f a b :=
|
||||||
|
comp_binary Q H (Hrefl a) (Hrefl b)
|
||||||
|
|
||||||
|
definition quotient_map {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(Q : is_quotient R abs rep) (f : A → A) (b : B) : B :=
|
||||||
|
abs (f (rep b))
|
||||||
|
|
||||||
|
theorem comp_quotient_map {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(Q : is_quotient R abs rep) {f : A → A}
|
||||||
|
(H : forall (a a' : A) (Ha : R a a'), R (f a) (f a'))
|
||||||
|
{a : A} (Ha : R a a) : quotient_map Q f (abs a) = abs (f a) :=
|
||||||
|
have H2 : R a (rep (abs a)), from R_rep_abs Q Ha,
|
||||||
|
have H3 : R (f a) (f (rep (abs a))), from H _ _ H2,
|
||||||
|
have H4 : abs (f a) = abs (f (rep (abs a))), from eq_abs Q H3,
|
||||||
|
symm H4
|
||||||
|
|
||||||
|
definition quotient_map_binary {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(Q : is_quotient R abs rep) (f : A → A → A) (b c : B) : B :=
|
||||||
|
abs (f (rep b) (rep c))
|
||||||
|
|
||||||
|
theorem comp_quotient_map_binary {A B : Type} {R : A → A → Prop} {abs : A → B} {rep : B → A}
|
||||||
|
(Q : is_quotient R abs rep) {f : A → A → A}
|
||||||
|
(H : forall (a a' b b' : A) (Ha : R a a') (Hb : R b b'), R (f a b) (f a' b'))
|
||||||
|
{a b : A} (Ha : R a a) (Hb : R b b) : quotient_map_binary Q f (abs a) (abs b) = abs (f a b) :=
|
||||||
|
have Ha2 : R a (rep (abs a)), from R_rep_abs Q Ha,
|
||||||
|
have Hb2 : R b (rep (abs b)), from R_rep_abs Q Hb,
|
||||||
|
have H2 : R (f a b) (f (rep (abs a)) (rep (abs b))), from H _ _ _ _ Ha2 Hb2,
|
||||||
|
symm (eq_abs Q H2)
|
||||||
|
|
||||||
|
theorem comp_quotient_map_binary_refl {A B : Type} {R : A → A → Prop} (Hrefl : reflexive R)
|
||||||
|
{abs : A → B} {rep : B → A} (Q : is_quotient R abs rep) {f : A → A → A}
|
||||||
|
(H : forall (a a' b b' : A) (Ha : R a a') (Hb : R b b'), R (f a b) (f a' b'))
|
||||||
|
(a b : A) : quotient_map_binary Q f (abs a) (abs b) = abs (f a b) :=
|
||||||
|
comp_quotient_map_binary Q H (Hrefl a) (Hrefl b)
|
||||||
|
|
||||||
|
opaque_hint (hiding rec rec_constant rec_binary quotient_map quotient_map_binary)
|
||||||
|
|
||||||
|
|
||||||
|
-- image
|
||||||
|
-- -----
|
||||||
|
|
||||||
|
-- has to be an abbreviation, so that fun_image_definition below will typecheck outside
|
||||||
|
-- the file
|
||||||
|
abbreviation image {A B : Type} (f : A → B) := subtype (fun b, ∃a, f a = b)
|
||||||
|
|
||||||
|
theorem image_inhabited {A B : Type} (f : A → B) (H : inhabited A) : inhabited (image f) :=
|
||||||
|
inhabited_intro (tag (f (default A)) (exists_intro (default A) rfl))
|
||||||
|
|
||||||
|
theorem image_inhabited2 {A B : Type} (f : A → B) (a : A) : inhabited (image f) :=
|
||||||
|
image_inhabited f (inhabited_intro a)
|
||||||
|
|
||||||
|
definition fun_image {A B : Type} (f : A → B) (a : A) : image f :=
|
||||||
|
tag (f a) (exists_intro a rfl)
|
||||||
|
|
||||||
|
theorem fun_image_def {A B : Type} (f : A → B) (a : A) :
|
||||||
|
fun_image f a = tag (f a) (exists_intro a rfl) := rfl
|
||||||
|
|
||||||
|
theorem elt_of_fun_image {A B : Type} (f : A → B) (a : A) : elt_of (fun_image f a) = f a :=
|
||||||
|
elt_of_tag _ _
|
||||||
|
|
||||||
|
theorem image_elt_of {A B : Type} {f : A → B} (u : image f) : ∃a, f a = elt_of u :=
|
||||||
|
has_property u
|
||||||
|
|
||||||
|
theorem fun_image_surj {A B : Type} {f : A → B} (u : image f) : ∃a, fun_image f a = u :=
|
||||||
|
subtype_destruct u
|
||||||
|
(take (b : B) (H : ∃a, f a = b),
|
||||||
|
obtain a (H': f a = b), from H,
|
||||||
|
(exists_intro a (tag_eq H')))
|
||||||
|
|
||||||
|
theorem image_tag {A B : Type} {f : A → B} (u : image f) : ∃a H, tag (f a) H = u :=
|
||||||
|
obtain a (H : fun_image f a = u), from fun_image_surj u,
|
||||||
|
exists_intro a (exists_intro (exists_intro a rfl) H)
|
||||||
|
|
||||||
|
theorem fun_image_eq {A B : Type} (f : A → B) (a a' : A)
|
||||||
|
: (f a = f a') ↔ (fun_image f a = fun_image f a') :=
|
||||||
|
iff_intro
|
||||||
|
(assume H : f a = f a', tag_eq H)
|
||||||
|
(assume H : fun_image f a = fun_image f a',
|
||||||
|
subst (subst (congr2 elt_of H) (elt_of_fun_image f a)) (elt_of_fun_image f a'))
|
||||||
|
|
||||||
|
theorem idempotent_image_elt_of {A : Type} {f : A → A} (H : ∀a, f (f a) = f a) (u : image f)
|
||||||
|
: fun_image f (elt_of u) = u :=
|
||||||
|
obtain (a : A) (Ha : fun_image f a = u), from fun_image_surj u,
|
||||||
|
calc
|
||||||
|
fun_image f (elt_of u) = fun_image f (elt_of (fun_image f a)) : {symm Ha}
|
||||||
|
... = fun_image f (f a) : {elt_of_fun_image f a}
|
||||||
|
... = fun_image f a : {iff_elim_left (fun_image_eq f (f a) a) (H a)}
|
||||||
|
... = u : Ha
|
||||||
|
|
||||||
|
theorem idempotent_image_fix {A : Type} {f : A → A} (H : ∀a, f (f a) = f a) (u : image f)
|
||||||
|
: f (elt_of u) = elt_of u :=
|
||||||
|
obtain (a : A) (Ha : f a = elt_of u), from image_elt_of u,
|
||||||
|
calc
|
||||||
|
f (elt_of u) = f (f a) : {symm Ha}
|
||||||
|
... = f a : H a
|
||||||
|
... = elt_of u : Ha
|
||||||
|
|
||||||
|
|
||||||
|
-- construct quotient from representative map
|
||||||
|
-- ------------------------------------------
|
||||||
|
|
||||||
|
theorem representative_map_idempotent {A : Type} {R : A → A → Prop} {f : A → A}
|
||||||
|
(H1 : ∀a, R a (f a)) (H2 : ∀a b, R a b ↔ R a a ∧ R b b ∧ f a = f b) (a : A)
|
||||||
|
: f (f a) = f a :=
|
||||||
|
symm (and_elim_right (and_elim_right (iff_elim_left (H2 a (f a)) (H1 a))))
|
||||||
|
|
||||||
|
theorem representative_map_idempotent_equiv {A : Type} {R : A → A → Prop} {f : A → A}
|
||||||
|
(H1 : ∀a, R a (f a)) (H2 : ∀a b, R a b → f a = f b) (a : A)
|
||||||
|
: f (f a) = f a :=
|
||||||
|
symm (H2 a (f a) (H1 a))
|
||||||
|
|
||||||
|
theorem representative_map_refl_rep {A : Type} {R : A → A → Prop} {f : A → A}
|
||||||
|
(H1 : ∀a, R a (f a)) (H2 : ∀a b, R a b ↔ R a a ∧ R b b ∧ f a = f b) (a : A)
|
||||||
|
: R (f a) (f a) :=
|
||||||
|
subst (representative_map_idempotent H1 H2 a) (H1 (f a))
|
||||||
|
|
||||||
|
theorem representative_map_image_fix {A : Type} {R : A → A → Prop} {f : A → A}
|
||||||
|
(H1 : ∀a, R a (f a)) (H2 : ∀a a', R a a' ↔ R a a ∧ R a' a' ∧ f a = f a') (b : image f)
|
||||||
|
: f (elt_of b) = elt_of b :=
|
||||||
|
idempotent_image_fix (representative_map_idempotent H1 H2) b
|
||||||
|
|
||||||
|
theorem representative_map_to_quotient {A : Type} {R : A → A → Prop} {f : A → A}
|
||||||
|
(H1 : ∀a, R a (f a)) (H2 : ∀a a', R a a' ↔ R a a ∧ R a' a' ∧ f a = f a')
|
||||||
|
: is_quotient _ (fun_image f) elt_of :=
|
||||||
|
let abs [inline] := fun_image f in
|
||||||
|
intro
|
||||||
|
(take u : image f,
|
||||||
|
obtain (a : A) (Ha : f a = elt_of u), from image_elt_of u,
|
||||||
|
have H : elt_of (abs (elt_of u)) = elt_of u, from
|
||||||
|
calc
|
||||||
|
elt_of (abs (elt_of u)) = f (elt_of u) : elt_of_fun_image _ _
|
||||||
|
... = f (f a) : {symm Ha}
|
||||||
|
... = f a : representative_map_idempotent H1 H2 a
|
||||||
|
... = elt_of u : Ha,
|
||||||
|
show abs (elt_of u) = u, from subtype_eq H)
|
||||||
|
(take u : image f,
|
||||||
|
show R (elt_of u) (elt_of u), from
|
||||||
|
obtain (a : A) (Ha : f a = elt_of u), from image_elt_of u,
|
||||||
|
subst Ha (@representative_map_refl_rep A R f H1 H2 a))
|
||||||
|
(take a a',
|
||||||
|
substi (fun_image_eq f a a') (H2 a a'))
|
||||||
|
|
||||||
|
-- TODO: fix these
|
||||||
|
-- e.g. in the next three lemmas, we should not need to specify the equivalence relation
|
||||||
|
-- but the class inference finds reflexive.class eq
|
||||||
|
theorem equiv_is_refl {A : Type} {R : A → A → Prop} (equiv : is_equivalence.class R) :=
|
||||||
|
@operations.refl _ R (@is_equivalence.is_reflexive _ _ equiv)
|
||||||
|
-- we should be able to write
|
||||||
|
-- @operations.refl _ R _
|
||||||
|
|
||||||
|
theorem equiv_is_symm {A : Type} {R : A → A → Prop} (equiv : is_equivalence.class R) :=
|
||||||
|
@operations.symm _ R (@is_equivalence.is_symmetric _ _ equiv)
|
||||||
|
|
||||||
|
theorem equiv_is_trans {A : Type} {R : A → A → Prop} (equiv : is_equivalence.class R) :=
|
||||||
|
@operations.trans _ R (@is_equivalence.is_transitive _ _ equiv)
|
||||||
|
|
||||||
|
theorem representative_map_equiv_inj {A : Type} {R : A → A → Prop}
|
||||||
|
(equiv : is_equivalence.class R) {f : A → A} (H1 : ∀a, R a (f a)) (H2 : ∀a b, R a b → f a = f b)
|
||||||
|
{a b : A} (H3 : f a = f b) : R a b :=
|
||||||
|
-- have symmR : symmetric R, from @relation.operations.symm _ R _,
|
||||||
|
have symmR : symmetric R, from equiv_is_symm equiv,
|
||||||
|
have transR : transitive R, from equiv_is_trans equiv,
|
||||||
|
show R a b, from
|
||||||
|
have H2 : R a (f b), from subst H3 (H1 a),
|
||||||
|
have H3 : R (f b) b, from symmR _ _ (H1 b),
|
||||||
|
transR _ _ _ H2 H3
|
||||||
|
|
||||||
|
theorem representative_map_to_quotient_equiv {A : Type} {R : A → A → Prop}
|
||||||
|
(equiv : is_equivalence.class R) {f : A → A} (H1 : ∀a, R a (f a)) (H2 : ∀a b, R a b → f a = f b)
|
||||||
|
: @is_quotient A (image f) R (fun_image f) elt_of :=
|
||||||
|
representative_map_to_quotient
|
||||||
|
H1
|
||||||
|
(take a b,
|
||||||
|
have reflR : reflexive R, from equiv_is_refl equiv,
|
||||||
|
have H3 : f a = f b → R a b, from representative_map_equiv_inj equiv H1 H2,
|
||||||
|
have H4 : R a b ↔ f a = f b, from iff_intro (H2 a b) H3,
|
||||||
|
have H5 : R a b ↔ R b b ∧ f a = f b,
|
||||||
|
from substi (symmi (and_inhabited_left _ (reflR b))) H4,
|
||||||
|
substi (symmi (and_inhabited_left _ (reflR a))) H5)
|
||||||
|
|
||||||
|
-- TODO: split this into another file -- it depends on hilbert
|
||||||
|
|
||||||
|
-- abstract quotient
|
||||||
|
-- -----------------
|
||||||
|
|
||||||
|
definition prelim_map {A : Type} (R : A → A → Prop) (a : A) :=
|
||||||
|
-- TODO: it is interesting how the elaborator fails here
|
||||||
|
-- epsilon (fun b, R a b)
|
||||||
|
@epsilon _ (nonempty_intro a) (fun b, R a b)
|
||||||
|
|
||||||
|
-- TODO: only needed R reflexive (or weaker: R a a)
|
||||||
|
theorem prelim_map_rel {A : Type} {R : A → A → Prop} (H : is_equivalence.class R) (a : A)
|
||||||
|
: R a (prelim_map R a) :=
|
||||||
|
have reflR : reflexive R, from equiv_is_refl H,
|
||||||
|
epsilon_spec (exists_intro a (reflR a))
|
||||||
|
|
||||||
|
-- TODO: only needed: R PER
|
||||||
|
theorem prelim_map_congr {A : Type} {R : A → A → Prop} (H1 : is_equivalence.class R) {a b : A}
|
||||||
|
(H2 : R a b) : prelim_map R a = prelim_map R b :=
|
||||||
|
have symmR : symmetric R, from equiv_is_symm H1,
|
||||||
|
have transR : transitive R, from equiv_is_trans H1,
|
||||||
|
have H3 : ∀c, R a c ↔ R b c, from
|
||||||
|
take c,
|
||||||
|
iff_intro
|
||||||
|
(assume H4 : R a c, transR b a c (symmR a b H2) H4)
|
||||||
|
(assume H4 : R b c, transR a b c H2 H4),
|
||||||
|
have H4 : (fun c, R a c) = (fun c, R b c), from funext (take c, iff_to_eq (H3 c)),
|
||||||
|
show @epsilon _ (nonempty_intro a) (λc, R a c) = @epsilon _ (nonempty_intro b) (λc, R b c),
|
||||||
|
from congr2 _ H4
|
||||||
|
|
||||||
|
definition quotient {A : Type} (R : A → A → Prop) : Type := image (prelim_map R)
|
||||||
|
|
||||||
|
definition quotient_abs {A : Type} (R : A → A → Prop) : A → quotient R :=
|
||||||
|
fun_image (prelim_map R)
|
||||||
|
|
||||||
|
definition quotient_elt_of {A : Type} (R : A → A → Prop) : quotient R → A := elt_of
|
||||||
|
|
||||||
|
theorem quotient_is_quotient {A : Type} (R : A → A → Prop) (H : is_equivalence.class R)
|
||||||
|
: is_quotient R (quotient_abs R) (quotient_elt_of R) :=
|
||||||
|
representative_map_to_quotient_equiv
|
||||||
|
H
|
||||||
|
(prelim_map_rel H)
|
||||||
|
(@prelim_map_congr _ _ H)
|
||||||
|
|
||||||
|
-- previously:
|
||||||
|
-- opaque_hint (hiding fun_image rec is_quotient prelim_map)
|
||||||
|
-- transparent: image, image_incl, quotient, quotient_abs, quotient_rep
|
||||||
|
|
||||||
|
end quotient
|
|
@ -38,7 +38,7 @@ section
|
||||||
assume (H2' : eq_rec_on H1' b1 = b2'),
|
assume (H2' : eq_rec_on H1' b1 = b2'),
|
||||||
show dpair a1 b1 = dpair a1 b2', from
|
show dpair a1 b1 = dpair a1 b2', from
|
||||||
calc
|
calc
|
||||||
dpair a1 b1 = dpair a1 (eq_rec_on H1' b1) : {symm (eq_rec_on_irrel H1' b1)}
|
dpair a1 b1 = dpair a1 (eq_rec_on H1' b1) : {symm (eq_rec_on_id H1' b1)}
|
||||||
... = dpair a1 b2' : {H2'}) H1)
|
... = dpair a1 b2' : {H2'}) H1)
|
||||||
b2 H1 H2
|
b2 H1 H2
|
||||||
|
|
||||||
|
|
|
@ -27,7 +27,7 @@ section
|
||||||
|
|
||||||
theorem tag_irrelevant {a : A} (H1 H2 : P a) : tag a H1 = tag a H2 := refl (tag a H1)
|
theorem tag_irrelevant {a : A} (H1 H2 : P a) : tag a H1 = tag a H2 := refl (tag a H1)
|
||||||
|
|
||||||
theorem tag_ext (a : subtype P) : Π(H : P (elt_of a)), tag (elt_of a) H = a :=
|
theorem tag_elt_of (a : subtype P) : Π(H : P (elt_of a)), tag (elt_of a) H = a :=
|
||||||
subtype_destruct a (take (x : A) (H1 : P x) (H2 : P x), refl _)
|
subtype_destruct a (take (x : A) (H1 : P x) (H2 : P x), refl _)
|
||||||
|
|
||||||
theorem tag_eq {a1 a2 : A} {H1 : P a1} {H2 : P a2} (H3 : a1 = a2) : tag a1 H1 = tag a2 H2 :=
|
theorem tag_eq {a1 a2 : A} {H1 : P a1} {H2 : P a2} (H3 : a1 = a2) : tag a1 H1 = tag a2 H2 :=
|
||||||
|
|
|
@ -4,5 +4,13 @@ logic.classes
|
||||||
Useful classes for general logical manipulations.
|
Useful classes for general logical manipulations.
|
||||||
|
|
||||||
* [inhabited](inhabited.lean) : inhabited types
|
* [inhabited](inhabited.lean) : inhabited types
|
||||||
|
* [nonempty](nonempty.lean) : nonempty type
|
||||||
* [decidable](decidable.lean) : decidable types
|
* [decidable](decidable.lean) : decidable types
|
||||||
* [congr](congr.lean) : congruences with respect to suitable relations
|
* [congr](congr.lean) : congruences with respect to suitable relations
|
||||||
|
|
||||||
|
Constructively, inhabited types have a witness, while nonempty types
|
||||||
|
are "proof irrelevant". Classically (assuming the axiom in
|
||||||
|
`logic.axioms.hilbert`) the two are equivalent. Type class inferences
|
||||||
|
are set up to use "inhabited" however, so users should use that to
|
||||||
|
declare that types have an element. Use "nonempty" in the hypothesis
|
||||||
|
of a theorem when the theorem does not depend on the witness chosen.
|
|
@ -14,7 +14,12 @@ inductive eq {A : Type} (a : A) : A → Prop :=
|
||||||
|
|
||||||
infix `=`:50 := eq
|
infix `=`:50 := eq
|
||||||
|
|
||||||
theorem eq_irrel {A : Type} {a : A} (H1 : a = a) : H1 = (refl a) := refl _
|
-- TODO: try this out -- shorthand for "refl _"
|
||||||
|
notation `rfl`:max := refl _
|
||||||
|
|
||||||
|
theorem eq_id_refl {A : Type} {a : A} (H1 : a = a) : H1 = (refl a) := rfl
|
||||||
|
|
||||||
|
theorem eq_irrel {A : Type} {a b : A} (H1 H2 : a = b) : H1 = H2 := rfl
|
||||||
|
|
||||||
theorem subst {A : Type} {a b : A} {P : A → Prop} (H1 : a = b) (H2 : P a) : P b :=
|
theorem subst {A : Type} {a b : A} {P : A → Prop} (H1 : a = b) (H2 : P a) : P b :=
|
||||||
eq_rec H2 H1
|
eq_rec H2 H1
|
||||||
|
@ -37,11 +42,17 @@ assume H : true = false,
|
||||||
definition eq_rec_on {A : Type} {a1 a2 : A} {B : A → Type} (H1 : a1 = a2) (H2 : B a1) : B a2 :=
|
definition eq_rec_on {A : Type} {a1 a2 : A} {B : A → Type} (H1 : a1 = a2) (H2 : B a1) : B a2 :=
|
||||||
eq_rec H2 H1
|
eq_rec H2 H1
|
||||||
|
|
||||||
theorem eq_rec_on_irrel {A : Type} {a : A} {B : A → Type} (H : a = a) (b : B a) : eq_rec_on H b = b :=
|
theorem eq_rec_on_id {A : Type} {a : A} {B : A → Type} (H : a = a) (b : B a) : eq_rec_on H b = b :=
|
||||||
@trans _ _ (eq_rec_on (refl a) b) _ (refl _) (refl _)
|
@trans _ _ (eq_rec_on (refl a) b) _ (refl _) (refl _)
|
||||||
|
|
||||||
theorem eq_rec_irrel {A : Type} {a : A} {B : A → Type} (H : a = a) (b : B a) : eq_rec b H = b :=
|
theorem eq_rec_id {A : Type} {a : A} {B : A → Type} (H : a = a) (b : B a) : eq_rec b H = b :=
|
||||||
eq_rec_on_irrel H b
|
eq_rec_on_id H b
|
||||||
|
|
||||||
|
theorem eq_rec_on_compose {A : Type} {a b c : A} {P : A → Type} (H1 : a = b) (H2 : b = c) (u : P a) :
|
||||||
|
eq_rec_on H2 (eq_rec_on H1 u) = eq_rec_on (trans H1 H2) u :=
|
||||||
|
(show ∀(H2 : b = c), eq_rec_on H2 (eq_rec_on H1 u) = eq_rec_on (trans H1 H2) u,
|
||||||
|
from eq_rec_on H2 (take (H2 : b = b), eq_rec_on_id H2 _))
|
||||||
|
H2
|
||||||
|
|
||||||
namespace eq_proofs
|
namespace eq_proofs
|
||||||
postfix `⁻¹`:100 := symm
|
postfix `⁻¹`:100 := symm
|
||||||
|
|
|
@ -1,8 +1,6 @@
|
||||||
----------------------------------------------------------------------------------------------------
|
|
||||||
-- Copyright (c) 2014 Microsoft Corporation. All rights reserved.
|
-- Copyright (c) 2014 Microsoft Corporation. All rights reserved.
|
||||||
-- Released under Apache 2.0 license as described in the file LICENSE.
|
-- Released under Apache 2.0 license as described in the file LICENSE.
|
||||||
-- Author: Jeremy Avigad
|
-- Author: Jeremy Avigad
|
||||||
----------------------------------------------------------------------------------------------------
|
|
||||||
|
|
||||||
import logic.connectives.prop
|
import logic.connectives.prop
|
||||||
|
|
||||||
|
@ -20,11 +18,11 @@ namespace is_reflexive
|
||||||
inductive class {T : Type} (R : T → T → Type) : Prop :=
|
inductive class {T : Type} (R : T → T → Type) : Prop :=
|
||||||
| mk : reflexive R → class R
|
| mk : reflexive R → class R
|
||||||
|
|
||||||
abbreviation app ⦃T : Type⦄ {R : T → T → Type} (C : class R) : reflexive R
|
abbreviation app ⦃T : Type⦄ {R : T → T → Type} (C : class R) : reflexive R :=
|
||||||
:= class_rec (λu, u) C
|
class_rec (λu, u) C
|
||||||
|
|
||||||
abbreviation infer ⦃T : Type⦄ {R : T → T → Type} {C : class R} : reflexive R
|
abbreviation infer ⦃T : Type⦄ {R : T → T → Type} {C : class R} : reflexive R :=
|
||||||
:= class_rec (λu, u) C
|
class_rec (λu, u) C
|
||||||
|
|
||||||
end is_reflexive
|
end is_reflexive
|
||||||
|
|
||||||
|
@ -33,11 +31,11 @@ namespace is_symmetric
|
||||||
inductive class {T : Type} (R : T → T → Type) : Prop :=
|
inductive class {T : Type} (R : T → T → Type) : Prop :=
|
||||||
| mk : symmetric R → class R
|
| mk : symmetric R → class R
|
||||||
|
|
||||||
abbreviation app ⦃T : Type⦄ {R : T → T → Type} (C : class R) ⦃x y : T⦄ (H : R x y) : R y x
|
abbreviation app ⦃T : Type⦄ {R : T → T → Type} (C : class R) ⦃x y : T⦄ (H : R x y) : R y x :=
|
||||||
:= class_rec (λu, u) C x y H
|
class_rec (λu, u) C x y H
|
||||||
|
|
||||||
abbreviation infer ⦃T : Type⦄ {R : T → T → Type} {C : class R} ⦃x y : T⦄ (H : R x y) : R y x
|
abbreviation infer ⦃T : Type⦄ {R : T → T → Type} {C : class R} ⦃x y : T⦄ (H : R x y) : R y x :=
|
||||||
:= class_rec (λu, u) C x y H
|
class_rec (λu, u) C x y H
|
||||||
|
|
||||||
end is_symmetric
|
end is_symmetric
|
||||||
|
|
||||||
|
@ -47,15 +45,51 @@ inductive class {T : Type} (R : T → T → Type) : Prop :=
|
||||||
| mk : transitive R → class R
|
| mk : transitive R → class R
|
||||||
|
|
||||||
abbreviation app ⦃T : Type⦄ {R : T → T → Type} (C : class R) ⦃x y z : T⦄ (H1 : R x y)
|
abbreviation app ⦃T : Type⦄ {R : T → T → Type} (C : class R) ⦃x y z : T⦄ (H1 : R x y)
|
||||||
(H2 : R y z) : R x z
|
(H2 : R y z) : R x z :=
|
||||||
:= class_rec (λu, u) C x y z H1 H2
|
class_rec (λu, u) C x y z H1 H2
|
||||||
|
|
||||||
abbreviation infer ⦃T : Type⦄ {R : T → T → Type} {C : class R} ⦃x y z : T⦄ (H1 : R x y)
|
abbreviation infer ⦃T : Type⦄ {R : T → T → Type} {C : class R} ⦃x y z : T⦄ (H1 : R x y)
|
||||||
(H2 : R y z) : R x z
|
(H2 : R y z) : R x z :=
|
||||||
:= class_rec (λu, u) C x y z H1 H2
|
class_rec (λu, u) C x y z H1 H2
|
||||||
|
|
||||||
end is_transitive
|
end is_transitive
|
||||||
|
|
||||||
|
namespace is_equivalence
|
||||||
|
|
||||||
|
inductive class {T : Type} (R : T → T → Type) : Prop :=
|
||||||
|
| mk : is_reflexive.class R → is_symmetric.class R → is_transitive.class R → class R
|
||||||
|
|
||||||
|
theorem is_reflexive {T : Type} {R : T → T → Type} {C : class R} : is_reflexive.class R :=
|
||||||
|
class_rec (λx y z, x) C
|
||||||
|
|
||||||
|
theorem is_symmetric {T : Type} {R : T → T → Type} {C : class R} : is_symmetric.class R :=
|
||||||
|
class_rec (λx y z, y) C
|
||||||
|
|
||||||
|
theorem is_transitive {T : Type} {R : T → T → Type} {C : class R} : is_transitive.class R :=
|
||||||
|
class_rec (λx y z, z) C
|
||||||
|
|
||||||
|
end is_equivalence
|
||||||
|
|
||||||
|
instance is_equivalence.is_reflexive
|
||||||
|
instance is_equivalence.is_symmetric
|
||||||
|
instance is_equivalence.is_transitive
|
||||||
|
|
||||||
|
namespace is_PER
|
||||||
|
|
||||||
|
inductive class {T : Type} (R : T → T → Type) : Prop :=
|
||||||
|
| mk : is_symmetric.class R → is_transitive.class R → class R
|
||||||
|
|
||||||
|
theorem is_symmetric {T : Type} {R : T → T → Type} {C : class R} : is_symmetric.class R :=
|
||||||
|
class_rec (λx y, x) C
|
||||||
|
|
||||||
|
theorem is_transitive {T : Type} {R : T → T → Type} {C : class R} : is_transitive.class R :=
|
||||||
|
class_rec (λx y, y) C
|
||||||
|
|
||||||
|
end is_PER
|
||||||
|
|
||||||
|
-- instance is_PER.is_symmetric
|
||||||
|
instance is_PER.is_transitive
|
||||||
|
|
||||||
|
|
||||||
-- Congruence for unary and binary functions
|
-- Congruence for unary and binary functions
|
||||||
-- -----------------------------------------
|
-- -----------------------------------------
|
||||||
|
|
Loading…
Add table
Reference in a new issue